Prevensi Perilaku Bullying Pada Siswa Sekolah Dasar Melalui Social Skill Training Dan Family Psycoeducation di Kota Padang - Renidayati Renidayati (Jurnal Pembangunan Nagari, 2018)
Bullying seems to have become an integral part of the lives of children today. The high incidence of bullying behavior in primary school-aged children in the family, school, and surrounding environment indicates the need for immediate interventions to address the problem of school-aged children. Some efforts should be made in the form of prevention, treatment and rehabilitations for victims of bullying behavior. One form of intervention that can be developed as an effort to prevent bullying behavior in school-aged children is Social Skill Training and Family Psycho education therapy. Through Social Skill Training and Family Psychoeducation can improve cognitive, psychomotor and affective school-aged children to prevent bullying behavior. Social Skill Training and Family Psycho education can be developed as a model in the prevention of Bullying behavior in school-aged children.